No effect of CBT‐based online self‐help training to reduce fear of cancer recurrence: First results of the CAREST multicenter randomized controlled trial. Issue 1 (13th November 2019) - van Helmondt, Sanne Jasperine; van der Lee, Marije Liesbeth; van Woezik, Rosalie Antonia Maria; Lodder, Paul; de Vries, Jolanda
Abstract: Objective: Fear of cancer recurrence (FCR) is a common consequence of surviving cancer; therefore, easily accessible self‐help training could help many cancer survivors deal with FCR at low costs. The CAncer REcurrence Self‐help Training (CAREST) trial evaluates the effectiveness of an online‐tailored self‐help training on the basis of evidence‐based cognitive behavioral therapy principles in breast cancer survivors. Also, possible predictors for benefitting from the online self‐help training were examined. Methods: This multicenter randomized controlled trial included 262 female breast cancer survivors, randomly assigned to either online self‐help training (n = 130) or care as usual (CAU; n = 132). Participants completed questionnaires at baseline (T0), 3 months (T1; after intervention), and 9 months (T2). The primary outcome was FCR (Fear of Cancer Recurrence Inventory Severity subscale). Both effectiveness and predictors were analyzed with latent growth curve modeling (LGCM) according to the intention‐to‐treat principle. Results: LGCM showed no differences between the average latent slope in both groups ( χ 2 1 = .23, P = .63), suggesting that the treatments did not differ in their change in FCR over time. Moreover, no differences were found in the effects of the predictors on the latent slope in both groups ( χ 2 1 = .12, P = .73), suggesting that no significant predictors were found for the effect of the intervention on FCR. Conclusion: There was no effect of the CBT‐based online self‐help training "Less fear after cancer" in the current study. Therefore, we recommend adding professional support to online interventions for FCR.